Self-lubricating wear-resistant coating for groove drum surface treatment and preparation method of self-lubricating wear-resistant coating
By applying a self-lubricating wear-resistant coating made of nickel-chromium borosilicate alloy powder and other materials on the surface of the tank cylinder, the problem of serious wear of the tank cylinder is solved, and the effect of improving hardness, wear resistance and extending service life is achieved.
Patent Information
- Application Number
- CN202411758579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The groove barrel is severely worn due to irregular changes in the spiral grooves and high-speed friction, making it a key consumable part in textile machinery.
Laser cladding technology is used to coat the self-lubricating wear-resistant coating on the surface of the tank cylinder, and materials such as nickel-chromium borosilicate alloy powder, modified titanium oxide powder, nano-titanium nitride powder and molybdenum disulfide powder are used to form a composite coating with high hardness and high wear resistance.
It significantly improves the hardness and wear resistance of the outer surface of the groove barrel, reduces wear conditions, and effectively extends the service life of the groove barrel.
Smart Images

Figure CN119571312A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coating material and a method for optimizing the surface of a grooved drum, in particular to a self-lubricating wear-resistant coating and a method for treating the surface of a grooved drum, belonging to the technical field of coating processing. Background Art
[0002] Grooved drum, also known as wire guide cam, is mainly suitable for various textile machinery such as chemical fiber texturing machines, rewinding machines, winding machines, yarn doubling machines, and covered yarn machines. It is one of the important winding components on the grooved drum winder. The yarn tension and winding density during winding are the main basis for measuring the quality of bobbin formation, and represent the movement law of the yarn during bobbin winding and the distribution of yarn loops on the bobbin. The shape of the spiral groove curve on it has a direct impact on the formation of the bobbin.
[0003] Since the depth and width of the spiral grooves of the drum are irregular, it is difficult to use machining methods, and the outer surface and the groove surface are easily worn out due to long-term high-speed friction with the yarn, making the drum one of the key loss parts in textile machinery. Preparing a friction-reducing and wear-resistant self-lubricating composite coating on the outer surface of the drum is an effective way to solve this problem. Therefore, it is necessary to propose a self-lubricating wear-resistant coating and a method for treating the surface of the drum to improve the wear resistance and durability of the outer surface of the drum and extend the service life of the drum in textile machinery and equipment. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide a self-lubricating wear-resistant coating and method for groove drum surface treatment to solve the problem of large groove drum loss and improve its comprehensive long-term performance.
[0005] The technical solution of the present invention is: a self-lubricating wear-resistant coating for groove drum surface treatment, comprising a groove drum body and a self-lubricating wear-resistant coating coated on the surface of the groove drum body, wherein the raw materials for preparing the self-lubricating wear-resistant coating include, by weight: 20 to 35 parts of nickel-chromium-boron-silicon alloy powder, 5 to 10 parts of modified titanium oxide powder, 7 to 15 parts of nano titanium nitride powder, 7 to 15 parts of molybdenum disulfide powder, and an appropriate amount of stabilizer and binder.
[0006] Furthermore, the above-mentioned self-lubricating wear-resistant coating for groove drum surface treatment, wherein: the modified titanium oxide powder is modified by N-type doping, which not only obtains a higher conductivity by improving the conductivity to eliminate the static electricity generated on the coating surface, making the flow of ions in the coating material smoother, thereby reducing the heat accumulation caused by the internal friction of the ions, reducing the loss of the material itself due to high temperature, but also provides a sufficient lubrication source for the cladding reaction of molybdenum disulfide, reduces the loss of molybdenum disulfide, and saves costs; the preparation method of the modified titanium oxide powder comprises the following steps:
[0007] Step S11: converting titanium metal into gaseous state by physical means such as evaporation and sputtering, and condensing to form titanium oxide powder during cooling.
[0008] Step S12: introducing electron donors (such as niobium, aluminum and other elements) to dope and modify the titanium oxide powder to improve the performance of the titanium oxide powder.
[0009] Furthermore, the above-mentioned self-lubricating wear-resistant coating for groove drum surface treatment, wherein: the nano titanium nitride powder has extremely high chemical stability, exhibits good corrosion resistance in most acid and alkali solutions, and helps to enhance the wear resistance of the formed coating. The preparation method of the nano titanium nitride powder comprises the following steps:
[0010] Step S21: weigh titanium dioxide raw materials, mix and crush the titanium dioxide into nanometer-scale powders by a high-energy ball mill, and then add a nitridation accelerator and stir evenly to obtain a mixture, wherein the mass of the nitridation accelerator accounts for 0.045% of the mass of the mixture.
[0011] Step S22: placing the mixture under an ammonia atmosphere and reacting at a temperature of 1200 to 1300° C. for 0.5 to 5 hours to obtain a reduction product;
[0012] Step S23: placing the reduction product under protective gas and cooling it to room temperature to obtain nano titanium nitride powder. The nanostructuring also helps to enhance the toughness and fracture resistance of the prepared coating.
[0013] Furthermore, in the above-mentioned self-lubricating wear-resistant coating for groove drum surface treatment, the stabilizer includes any one or a combination of at least two of an organic antimony stabilizer, an organic tin stabilizer and a rare earth stabilizer.
[0014] Furthermore, in the above-mentioned self-lubricating and wear-resistant coating for groove drum surface treatment, the binder is an organic binder.
[0015] Furthermore, in the above-mentioned self-lubricating and wear-resistant coating for groove drum surface treatment, the organic binder is prepared from cellulose acetate and diacetone alcohol in a mass ratio of 1:1.
[0016] The present invention also provides a method for preparing a self-lubricating wear-resistant coating for groove drum surface treatment, the preparation method comprising the following steps:
[0017] Step 1: Weigh 20 to 35 parts of nickel-chromium-borosilicate alloy powder, 5 to 10 parts of modified titanium oxide powder, 7 to 15 parts of nano titanium nitride powder and 7 to 15 parts of molybdenum disulfide powder, mix them thoroughly, and then use a high-energy ball mill (the speed of the high-energy ball mill is 200 to 400 r / min) to mix and ball mill for 0.5 to 1 h, and then add a stabilizer to obtain a mixed powder.
[0018] Step 2: Pre-treat the oxide impurities formed on the surface of the drum body with a corrosive agent (the corrosive agent is used to efficiently clean the oxide impurities, thereby improving the coating efficiency and quality of the drum body surface), and then grind, polish and clean it for coating operations.
[0019] Step 3: Use a binder to pre-place the mixed powder on the surface of the drum body (the pre-coating treatment can determine the uniformity of the coating thickness and avoid uneven thickness, thereby maximizing the overall effect of the coating), with a thickness of 0.8 to 1.2 mm. Finally, place the pre-placed coating in a drying oven for heat preservation and drying.
[0020] Step 4: Turn on the fiber laser in the laser cladding device, focus the laser beam on the surface of the nickel alloy substrate, and use the laser cladding powder feeder to deliver the cladding powder to the laser spot on the surface of the groove drum. Set the process parameters of the laser beam and start laser cladding in the protective gas (the flow rate of the protective gas is 15L / min). After the laser cladding process is completed, a self-lubricating and wear-resistant coating is formed on the groove drum body.
[0021] Furthermore, in the above-mentioned method for preparing the self-lubricating wear-resistant coating for the surface treatment of the drum, the temperature of the heat preservation and drying is 70 to 100° C., and the heat preservation and drying time is 1.5 to 2 hours.
[0022] Furthermore, in the above-mentioned method for preparing the self-lubricating wear-resistant coating for groove drum surface treatment, the corrosive agent includes hydrofluoric acid and hydrochloric acid, and the volume ratio of the hydrofluoric acid to the hydrochloric acid is 1:1.
[0023] Furthermore, the above-mentioned method for preparing the self-lubricating wear-resistant coating for groove drum surface treatment, wherein: the laser cladding technology has the advantages of high energy density, low heat input, small distortion and small heat affected zone, and the process parameters of the laser cladding are: power of 1300-1600W, scanning speed of 10-15mm / s, defocus of 30-35mm, and overlap rate of multi-pass cladding of 50%.
[0024] In this way, by adopting the technical solution of the present invention, a cladding material made by laser cladding and adding modified titanium oxide powder mixed with nickel-chromium-boron-silicon alloy powder, nano titanium nitride powder and molybdenum disulfide powder is coated on the outer surface of the groove drum body to form a self-lubricating and wear-resistant coating with high hardness and high wear resistance, so as to extend the service life of the groove drum.
[0025] Compared with the prior art, after adopting the technical solution of the present invention, the self-lubricating wear-resistant coating is a composite coating, in which the reinforcing phase and the lubricating phase of the coating significantly improve the hardness and wear resistance of the outer surface of the groove drum, solve the groove drum wear problem occurring during the lubrication process, and effectively extend the service life of the groove drum. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the groove drum structure of the present invention;
[0027] Figure 2 The present invention is a flow chart of the method for preparing the self-lubricating wear-resistant coating.
[0028] The meanings of the reference numerals in the figure are: 1-groove barrel body, 2-connecting thread groove, 3-self-lubricating wear-resistant coating, 4-spiral groove, 5-groove hole. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings to make it easier to understand and grasp. Figure 1 It is a structural diagram of the grooved drum involved in this case, wherein components such as the connecting thread groove 2, the spiral groove 4 and the groove hole 5 are commonly used ones generally known to ordinary technicians in the field, and there is no special requirement for them in this case. Figure 2 The present invention is a flow chart of the method for preparing the self-lubricating wear-resistant coating, which mainly includes the steps of weighing and preparing raw materials, treating the surface of the grooved drum, pre-plating, laser cladding and plating.
[0030] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described below in conjunction with specific examples, but it should not be understood that the protection scope of the above subject matter of the present invention is limited to the following examples. Among them, the materials or parts used are commercially available or homemade using methods known in the industry.
[0031] Example 1
[0032] (i) Preparation of modified titanium oxide powder by N-type doping: Titanium metal is converted into gas by physical means such as evaporation and sputtering, and condensed to form titanium oxide powder during cooling. Aluminum element electron donor is introduced into the titanium oxide powder to obtain modified titanium oxide powder.
[0033] (ii) Preparation of nano titanium nitride powder: Weigh the required titanium dioxide raw material, mix and crush the titanium dioxide into nanometer-scale powder by a high-energy ball mill, add a nitriding accelerator and stir evenly to obtain a mixture, wherein the mass of the nitriding accelerator accounts for 0.045% of the mass of the mixture, place the mixture under an ammonia atmosphere, and react at a temperature of 1200°C for 0.5h to obtain a reduction product, and then place the reduction product under a protective gas and cool to room temperature to obtain nano titanium nitride powder.
[0034] (III) Weigh 20 parts of nickel-chromium-borosilicate alloy powder, 5 parts of modified titanium oxide powder, 7 parts of nano titanium nitride powder and 7 parts of molybdenum disulfide powder, mix them thoroughly, and then use a high-energy ball mill at a rotation speed of 200 r / min for 0.5 h, and then add an organic antimony stabilizer to obtain a mixed powder.
[0035] (iv) Pre-treating the oxide impurities formed on the surface of the drum body with a corrosive agent made of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:1, and then grinding, polishing and cleaning it for coating.
[0036] (V) The mixed powder is pre-placed on the surface of the drum body using a binder with a thickness of 0.8 mm. Finally, the pre-placed coating is placed in a drying oven and kept dry at 70°C for 1.5 hours.
[0037] (six) Turn on the fiber laser in the laser cladding device, focus the laser beam on the surface of the nickel alloy substrate, and the laser cladding powder feeder delivers the cladding powder to the laser spot on the surface of the groove drum body 1 (where the connecting thread groove 2, spiral groove 4 and groove hole 5 opened on the groove drum body 1 have a dead angle range, and the above structures all use an angle-adjustable laser beam instrument to perform corresponding cladding treatment to improve the coating uniformity and thick coating efficiency). The process parameters of the laser beam are set to be 1300W, 10mm / s, 30mm, and 50% overlap rate of multi-pass cladding. Laser cladding is started in a protective gas with a flow rate of 15L / min (where the protective gas is argon). After the laser cladding process is completed, a self-lubricating and wear-resistant coating 3 is formed on the groove drum body 1 to obtain a groove drum after coating.
[0038] Example 2
[0039] (i) Preparation of modified titanium oxide powder by N-type doping: Titanium metal is converted into gas by physical means such as evaporation and sputtering, and condensed to form titanium oxide powder during cooling. Niobium element electron donor is introduced into the titanium oxide powder to obtain modified titanium oxide powder.
[0040] (ii) Preparation of nano titanium nitride powder: Weigh the required titanium dioxide raw material, mix and crush the titanium dioxide into nanometer-scale powder by a high-energy ball mill, add a nitriding accelerator and stir evenly to obtain a mixture, wherein the mass of the nitriding accelerator accounts for 0.045% of the mass of the mixture, place the mixture under an ammonia atmosphere, and react at a temperature of 1250°C for 3.5h to obtain a reduction product, and then place the reduction product under a protective gas and cool to room temperature to obtain nano titanium nitride powder.
[0041] (III) Weigh 28 parts of nickel-chromium-borosilicate alloy powder, 8 parts of modified titanium oxide powder, 12 parts of nano titanium nitride powder and 12 parts of molybdenum disulfide powder, mix them thoroughly, and then use a high-energy ball mill at a rotation speed of 300 r / min for 0.8 h, and then add an organic tin stabilizer to obtain a mixed powder.
[0042] (iv) Pre-treating the oxide impurities formed on the surface of the drum body with a corrosive agent made of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:1, and then grinding, polishing and cleaning it for coating.
[0043] (V) The mixed powder is pre-placed on the surface of the drum body using a binder with a thickness of 1 mm. Finally, the pre-placed coating is placed in a drying oven and kept dry at 80°C for 1.8 hours.
[0044] (six) Turn on the fiber laser in the laser cladding device, focus the laser beam on the surface of the nickel alloy substrate, and the laser cladding powder feeder delivers the cladding powder to the laser spot on the surface of the groove drum (wherein the connecting thread groove 2, spiral groove 4 and groove hole 5 opened on the groove drum body 1 have a dead angle range, and the above structures all use an angle-adjustable laser beam instrument to perform corresponding cladding treatment to improve the coating uniformity and thick coating efficiency), set the process parameters of the laser beam, the power is 1400W, the scanning speed is 13mm / s, the defocus amount is 32mm, the overlap rate of multi-pass cladding is 50%, and start laser cladding in a protective gas with a flow rate of 15L / min (wherein the protective gas is argon). After the laser cladding process is completed, a self-lubricating and wear-resistant coating 3 is formed on the groove drum body 1 to obtain a groove drum after coating.
[0045] Example 3
[0046] (i) Preparation of modified titanium oxide powder by N-type doping: Titanium metal is converted into gas by physical means such as evaporation and sputtering, and condensed to form titanium oxide powder during cooling. Aluminum element electron donor is introduced into the titanium oxide powder to obtain modified titanium oxide powder.
[0047] (ii) Preparation of nano titanium nitride powder: Weigh the required titanium dioxide raw material, mix and crush the titanium dioxide into nanometer-scale powder by a high-energy ball mill, add a nitriding accelerator and stir evenly to obtain a mixture, wherein the mass of the nitriding accelerator accounts for 0.045% of the mass of the mixture, place the mixture under an ammonia atmosphere, and react at a temperature of 1300°C for 5h to obtain a reduction product, and then place the reduction product under a protective gas and cool to room temperature to obtain nano titanium nitride powder.
[0048] (III) Weigh 35 parts of nickel-chromium-borosilicate alloy powder, 10 parts of modified titanium oxide powder, 15 parts of nano-titanium nitride powder and 15 parts of molybdenum disulfide powder, mix them thoroughly, and then use a high-energy ball mill at a rotation speed of 400 r / min for 1 hour, and then add a rare earth stabilizer to obtain a mixed powder.
[0049] (iv) Pre-treating the oxide impurities formed on the surface of the drum body with a corrosive agent made of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:1, and then grinding, polishing and cleaning it for coating.
[0050] (V) Using a binder, the mixed powder is pre-placed on the surface of the drum body with a thickness of 1.2 mm. Finally, the pre-placed coating is placed in a drying oven and kept dry at 100°C for 2 hours.
[0051] (six) Turn on the fiber laser in the laser cladding device, focus the laser beam on the surface of the nickel alloy substrate, and the laser cladding powder feeder delivers the cladding powder to the laser spot on the surface of the groove drum (wherein the connecting thread groove 2, spiral groove 4 and groove hole 5 opened on the groove drum body 1 have a dead angle range, and the above structures all use an angle-adjustable laser beam instrument to perform corresponding cladding treatment to improve the coating uniformity and thick coating efficiency), set the process parameters of the laser beam, the power is 1600W, the scanning speed is 15mm / s, the defocus amount is 35mm, the overlap rate of multi-pass cladding is 50%, and laser cladding is started in a protective gas with a flow rate of 15L / min (wherein the protective gas is argon). After the laser cladding process is completed, a self-lubricating and wear-resistant coating 3 is formed on the groove drum body 1 to obtain a groove drum after coating.
[0052] Comparative Example 1
[0053] Ordinary grooved drums that have not undergone any coating or plating treatment can be purchased on the market or made at home.
[0054] The performance tests of the above embodiments and comparative examples are as follows:
[0055] (I) Hardness tests were performed on the outer surfaces of the grooved drums of Examples 1 to 3 and Comparative Example 1. Metallographic specimens were cut perpendicularly to the outer surfaces of the grooved drums using a wire cutting machine. The microhardness of the composite coating was tested along the cross-section of each metallographic specimen using a microhardness tester (with a loading load of 280 g and a holding time of 18 s). The hardness of the outer surfaces of the grooved drums of Examples 1 to 3 was significantly better than that of the outer surface of the grooved drum of the comparative example.
[0056] (ii) The friction degree of the outer surface of the grooved drum of the present embodiments 1 to 3 and the comparative example 1 was tested. The friction and wear test was carried out on the outer surface of each grooved drum on a multifunctional friction and wear testing machine (the loading load was 600g, the rotation speed was 120r / min, the wear scar diameter was 5mm, the time was 25min, and the grinding ball was ceramic WC). The amount of wear generated was weighed by an analytical balance. Among them, the friction coefficients of embodiments 1 to 3 were relatively stable, and the wear weight of the outer surface of the grooved drum of embodiments 1 to 3 was significantly lower than that of the outer surface of the grooved drum of the comparative example. Therefore, it can be concluded that the wear resistance of the grooved drum of embodiments 1 to 3 is significantly better than that of the grooved drum of the comparative example.
[0057] In the technical solution of the present invention, the cladding material of adding modified titanium oxide powder mixed with nickel-chromium-boron-silicon alloy powder, nano titanium nitride powder and molybdenum disulfide powder is the technical key of this case. Figure 1The grooved drum body 1 coated with a self-lubricating and wear-resistant coating is shown. Figure 2 The process flow of preparing the self-lubricating wear-resistant coating is shown. By using laser cladding, a good wear-resistant composite coating can be prepared on the surface of the groove drum body 1, which is reinforced by various intermetallic compounds and lubricated by various non-metallic compounds, and is combined with the metal material on the surface of the groove drum body 1. For the connecting thread groove 2, spiral groove 4 and groove hole 5 provided on the groove drum body 1, ordinary technicians in this field can make conventional settings according to the existing technology. There are no special requirements for the model selection and combined use in this case.
[0058] In this way, by adopting the technical solution of the present invention, a cladding material made by adding modified titanium oxide powder mixed with nickel-chromium-boron-silicon alloy powder, nano titanium nitride powder and molybdenum disulfide powder is coated on the outer surface of the groove drum body 1 through laser cladding to form a high-hardness, high-wear-resistant self-lubricating wear-resistant coating 3 to extend the service life of the groove drum.
[0059] From the above description, it can be found that compared with the prior art, after adopting the technical solution of the present invention, the self-lubricating wear-resistant coating is a composite coating, in which the reinforcing phase and the lubricating phase of the coating significantly improve the hardness and wear resistance of the outer surface of the groove drum, solve the groove drum wear problem occurring during the lubrication process, and effectively extend the service life of the groove drum.
[0060] The technical scheme, working process and implementation effect of the present invention are described in detail above. It should be noted that what is described is only a typical example of the present invention. In addition, the present invention may also have many other specific implementation methods. Any technical scheme formed by equivalent replacement or equivalent transformation falls within the scope of protection required by the present invention.
Claims
1. A self-lubricating and wear-resistant coating for surface treatment of a grooved drum, coated on the surface of a grooved drum body (1), characterized in that: The raw materials for preparing the self-lubricating wear-resistant coating (3) include, by weight: 20-35 parts of nickel-chromium-boron-silicon alloy powder; 5-10 parts of modified titanium oxide powder; 7-15 parts of nano titanium nitride powder; 7-15 parts of molybdenum disulfide powder; Appropriate amount of stabilizer and binder.
2. The self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 1, characterized in that: The modified titanium oxide powder is modified by N-type doping, and the preparation method thereof comprises the following steps: Step S11: converting titanium metal into gaseous state by physical means such as evaporation and sputtering, and condensing to form titanium oxide powder during cooling; Step S12: introducing an electron donor to dope the modified titanium oxide powder.
3. The self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 1, characterized in that: The preparation method of the nano titanium nitride powder comprises the following steps: Step S21: weighing titanium dioxide raw materials, mixing and crushing the titanium dioxide into nano-scale powders by a high-energy ball mill, and then adding a nitridation accelerator and stirring uniformly to obtain a mixture; Step S22: placing the mixture under an ammonia atmosphere and reacting at a temperature of 1200 to 1300° C. for 0.5 to 5 hours to obtain a reduction product; Step S23: placing the reduction product under protective gas and cooling it to room temperature to obtain nano titanium nitride powder.
4. The self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 1, characterized in that: The stabilizer includes any one of an organic antimony stabilizer, an organic tin stabilizer and a rare earth stabilizer, or a combination of at least two of them.
5. The self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 1, characterized in that: The binder is an organic binder.
6. The self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 5, characterized in that: The organic binder is prepared from cellulose acetate and diacetone alcohol in a mass ratio of 1:
1.
7. A method for preparing a self-lubricating wear-resistant coating for groove drum surface treatment, characterized in that The following steps are involved: Step 1: Weigh 20 to 35 parts of nickel-chromium-borosilicate alloy powder, 5 to 10 parts of modified titanium oxide powder, 7 to 15 parts of nano titanium nitride powder and 7 to 15 parts of molybdenum disulfide powder, mix them thoroughly, and then use a high-energy ball mill to mix and mill them for 0.5 to 1 hour, and then add a stabilizer to obtain a mixed powder; Step 2: pre-treating the oxide impurities formed on the surface of the drum body (1) with an etchant, and then grinding, polishing and cleaning it for coating; Step 3: pre-dispose the mixed powder on the surface of the drum body (1) with a binder to a thickness of 0.8 to 1.2 mm, and finally place the pre-disposed coating in a drying oven for heat preservation and drying; Step 4: Turn on the fiber laser in the laser cladding device, focus the laser beam on the surface of the nickel alloy substrate, and use the laser cladding powder feeder to deliver the cladding powder to the laser spot on the surface of the groove drum (1). Set the process parameters of the laser beam and start laser cladding in a protective gas. After the laser cladding process is completed, a self-lubricating and wear-resistant coating (3) is formed on the groove drum body (1).
8. The method for preparing the self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 7, characterized in that: In step 2, the corrosive agent includes hydrofluoric acid and hydrochloric acid, and the volume ratio of the hydrofluoric acid to the hydrochloric acid is 1:
1.
9. The method for preparing the self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 7, characterized in that: The temperature of the heat preservation and drying in step 3 is 70-100° C., and the heat preservation and drying time is 1.5-2 hours.
10. The method for preparing the self-lubricating and wear-resistant coating for groove drum surface treatment according to claim 7, characterized in that: The process parameters of the laser cladding in step 4 are: power of 1300-1600 W, scanning speed of 10-15 mm / s, defocusing amount of 30-35 mm, and overlap rate of multi-pass cladding of 50%.